Delinquency of Constitutional Court Decision Number 90/PUU-XXI/2023 on Age Limit Requirements for Presidential and Vice Presidential Candidature - Juanda; Nina Zainab (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The Constitutional Court is an institution of judicial power which has a judicial function to uphold law and justice. Law Number 24 of 2003 explains that the duties and functions of the Constitutional Court are to handle constitutional cases regarding certain constitutional matters in order to safeguard the constitution so that it is implemented responsibly in accordance with the will of the people and democratic ideals. One of the powers of the Constitutional Court is the authority of